Frequency of Respiratory Syncytial Virus Among Hospitalized Children with Acute Lower Respiratory Tract Infections - Hussain, Murtaza; Malik, Qudrat Ullah; Khan, Qamar uz Zaman; Mumtaz, Shaista; Abbas, Muhammad; Bashir, Junaid (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of respiratory syncytial virus (RSV) among hospitalized children with acute lower respiratory tract infections (ALRI) and associated risk factors. Study Design: Comparative cross-sectional study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jul 2019 to Aug 2020. Methodology: After approval from the Ethical Review Board, 126 children were included in the study. Nasopharyngeal aspirates were collected from children. The direct immunofluorescence method was utilized to detect intracellular viral antigens of the respiratory syncytial virus. In addition, the presence of symptoms and history for identification of the presence or absence of risk factors was recorded. Results: 57(45.2%) patients were found to be respiratory syncytial virus positive, and 69(54.8%) were respiratory syncytial virus negative. Significant differences were found in symptoms between RSV-positive and negative children (p=0.001). Conclusion: Respiratory syncytial virus was among the leading causes of children hospitalized with acute lower respiratory tract infections, with fever and recurrent wheezing as the most common symptoms.